TEACHING SPEECH SKILLS USING ROLE MODELING/ ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø·Ø±ÙŠÙ‚Ø© ØªÙ…Ø«ÙŠÙ„ Ø§Ù„Ø£Ø¯ÙˆØ§Ø± - Maimunah, Iffat (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Teaching Arabic at the Islamic university aims to understand Islamic books written in Arabic as well as improve language skills: listening, speaking, reading and writing. Previous research conducted by researchers showed the weakness of students in speaking. The teaching and learning process cause this. The teacher does not use various strategies. He only tells about lessons, limited opportunities for students to talk in class and their respective motivations to talk and discuss in class. The research conducted by this researcher aims to improve speaking skills through role-playing strategies. Role-playing is one of the most effective and exciting teaching methods that help us in the learning process, especially in developing speaking skills. The subjects of this study were students of the Islamic State University of Malang, Indonesia Faculty of Economics, EKA class 3. Using two cycles each containing four methods, namely: planning, implementation, observation, and reflection. The results of this study indicate that role-playing strategies are useful in improving students' speaking skills. During the role-playing, they do it with confidence without feeling embarrassed or worried, and they can speak fluently, even they can work together to improve their speaking skills while acting in the teaching process.Â Keywords: role-playing; teaching speaking skills; teaching strategies